Financial Performance as Mediator: The Role of Corporate Social Responsibility, Audit Quality, and Financial Distress in Islamic Finance Tax Aggressiveness - Suhadi, Suhadi; Januarti, Indira; SET, Fuad; Hardiningsih, Pancawati (Ekonomi Syariah IAIN Kudus, 2024)
This study aims to examine the influence of Corporate Social Responsibility (CSR), audit quality, and financial distress on tax aggressiveness with financial performance as a mediating variable. This research employs quantitative methods with a sample size of 168 companies listed on the Indonesian Sharia Stock Index (ISSI) from 2020-2022. Data were processed using multiple linear regression, and Sobel tests for mediation analysis. The results show that CSR and audit quality have a significant positive influence on financial performance. Meanwhile, financial distress has a significant negative effect on tax aggressiveness. CSR has a significant negative influence on the Effective Tax Rate (ETR). Audit quality has a significant positive influence on ETR, and financial distress also has a significant positive effect on ETR. Meanwhile, financial performance has not been proven to mediate CSR against tax aggressiveness. Theoretically, these findings suggest that financial performance is not a significant channel for understanding how CSR affects tax aggressiveness. In practical terms, this means that when a company conducts CSR activities, its impact on the tax strategy is not mediated by how well the company performs financially.